Psychological evaluation in childhood migraine – steps towards a psychological profile of the child migraineur - Smaranda Antonia Nita; Raluca Ioana Teleanu; Ovidiu Alexandru Bajenaru (Romanian Journal of Neurology, 2020)
Migraine can affect children and have an impact on their quality of life. Psychological and psychiatric comorbidities have been identified over the years, in association with migraine. Objective. To evaluate the possible relations between migraine and emotional disorders, in children. Material and methods. Eighteen patients aged 5-17 were recruited for the migraine group and sixteen age matched patients with no criteria for migraine or any underlying organic disorder, who were diagnosed with emotional disorders, were enrolled in the control group. The patients underwent psychological evaluation, which included use of projective diagnostic tests (tree, family and person drawings) and the ASEBA – CBCL/ YSR questionnaires, the results of which were noted in the form of raw scores, percentiles and T scores, and the results were analyzed for anxiety and introversion scales. Outcomes. For the anxiety scale, the mean ASEBA score was lower in migraine patients, compared to controls (p = 0.083), while the percentiles on the same scale were similar between the two groups (p = 0.480). For the introversion scale, the mean ASEBA score was lower in the migraine group, compared to controls (p = 0.059) and percentiles were lower in the migraine group (p = 0.036). Conclusions. Clinical observations and scores recorded through the ASEBA questionnaires pleaded for a psychological profile of migraine patients, yet the statistical analysis did not reveal significant results in this direction. However, the study opens up a road towards a more thorough assessment of migraine pediatric patients, which should include a psychological evaluation.